Construct validity of the Free and Cued Selective Reminding Test in older adults with memory complaints. Issue 2 (12th November 2015) - Clerici, Francesca; Ghiretti, Roberta; Di Pucchio, Alessandra; Pomati, Simone; Cucumo, Valentina; Marcone, Alessandra; Vanacore, Nicola; Mariani, Claudio; Cappa, Stefano Francesco
Abstract : Introduction: The Free and Cued Selective Reminding Test (FCSRT) is the memory test recommended by the International Working Group on Alzheimer's disease (AD) for the detection of amnestic syndrome of the medial temporal type in prodromal AD. Assessing the construct validity and internal consistency of the Italian version of the FCSRT is thus crucial. Methods: The FCSRT was administered to 338 community‐dwelling participants with memory complaints (57% females, age 74.5 ± 7.7 years), including 34 with AD, 203 with Mild Cognitive Impairment, and 101 with Subjective Memory Impairment. Internal Consistency was estimated using Cronbach's alpha coefficient. To assess convergent validity, five FCSRT scores (Immediate Free Recall, Immediate Total Recall, Delayed Free Recall, Delayed Total Recall, and Index of Sensitivity of Cueing) were correlated with three well‐validated memory tests: Story Recall, Rey Auditory Verbal Learning test, and Rey Complex Figure (RCF) recall (partial correlation analysis). To assess divergent validity, a principal component analysis (an exploratory factor analysis) was performed including, in addition to the above‐mentioned memory tasks, the following tests: Word Fluencies, RCF copy, Clock Drawing Test, Trail Making Test, Frontal Assessment Battery, Raven Coloured Progressive Matrices, and Stroop Colour‐Word Test. Results: Cronbach's alpha coefficients for immediate recalls (IFR and ITR) and delayed recalls (DFR and DTR) were, respectively, .84 and .81. All FCSRT scores were highly correlated with those of the three well‐validated memory tests. The factor analysis showed that the FCSRT does not load on the factors saturated by non‐memory tests. Conclusions: These findings indicate that the FCSRT has a good internal consistency and has an excellent construct validity as an episodic memory measure.